Respuesta :
3x-5y =15
2x-y=-4
multiply the equation by 5 and then subtract equation 2 from equation 1
so 3x-5y =15
10x-5y =-20
-7x =35 x =-5
plug in the value of x in the second equation -10 -y =-4 - y= -4 +10 y =-6
x=-5 y=-6
2x-y=-4
multiply the equation by 5 and then subtract equation 2 from equation 1
so 3x-5y =15
10x-5y =-20
-7x =35 x =-5
plug in the value of x in the second equation -10 -y =-4 - y= -4 +10 y =-6
x=-5 y=-6
Answer:
(−5, −6)
Step-by-step explanation:
GIVEN : [tex]3x-5y = 15[/tex]
[tex]2x-y = -4[/tex]
SOLUTION:
[tex]3x-5y = 15[/tex] ------EQUATION 1
[tex]2x-y = -4[/tex] ------ EQUATION 2
Now multiply the equation 2 by 5
⇒ [tex]5(2x-y = -4)[/tex]
⇒[tex]10x-5y = -20[/tex] ---(a)
Now , subtract (a) from equation i.e
[tex]3x-5y-15-(10x-5y+20) = 0[/tex]
[tex]3x-5y-15-10x+5y-20) = 0[/tex]
[tex] -7x-35 = 0[/tex]
[tex] -7x=35[/tex]
[tex]x=\frac{35}{-7}[/tex]
[tex] x=-5 [/tex]
put x = - 5 in equation 1 to get value of y
[tex]3(-5)-5y = 15[/tex]
[tex]-15-5y = 15[/tex]
[tex]-5y = 15+15[/tex]
[tex]-5y = 30[/tex]
[tex]y = \frac{30}{-5}[/tex]
[tex]y = -6[/tex]
Thus (x,y) =(-5,-6) is a solution.